Proceedings of the 11th International Congress on the Archaeology of the Ancient Near East: Vol. 2: Field Reports. Islamic Archaeology - Otto, Adelheid; Herles, Michael; Kaniuth, Kai; Korn, Lorenz; Heidenreich, Anja (Proceedings of the International Congress on the Archaeology of the Ancient Near East, 2020)
Cover -- Title Pages -- Contents of Vol. 2 -- Foreword to Section 7 - Field Reports -- Section 7: Field Reports -- Aradetis Orgora: Lithic Artefacts from a Site of the Southern Caucasus, Georgia -- The Place of "Dragon Stone" Sanctuaries in Context of Cultic Areas of Ancient Armenia -- Gulf Connections at Tell Khaiber. Interpreting Standardised Pottery Styles in the Sealand Period -- Ban Qala: A Late Chalcolithic Site in the Qara Dagh Valley of Iraqi Kurdistan -- The Sanctuary and Cemetery at Kal-e Chendar, Shami (Khuzestan, Iran) -- Seven Excavation Campaigns at Abu Tbeirah -- Excavations at Gonur Depe. A BMAC Bronze Age Site in Turkmenistan in 2014-2015: Necropolis and Residential Areas in the South-West -- Early Bronze Age Graves at Doghlauri (Georgia): Results of the 2012-2015 Salvage Excavations -- 2017 Survey of Two Prehistoric Sites in Western Cyprus: Stroumpi-Pigi-Agios Andronikos and Makounta-Voules-Mersinoudia -- The Excavations at Tel Rekhesh, Israel: The Results of 2013-2017 Seasons -- Zincirli Höyük, Ancient Sam'al: A Preliminary Report on the 2017 Excavation Season -- Why Did They Still Use the Tell? An Analysis of Changes in Post-Chalcolithic Settlement at Çatalhöyük, Turkey -- Preliminary Report of the "Forgotten Borderlands" Project in Guria and Adjara (Georgia). Several Remarks on the Results of the Structural Survey at Tsikhisdziri -- A New Royal and Religious Space in Ayanis Citadel: The Hall With Podium -- The Outdoor Communal Neolithic Cemetery of Tell el-Kerkh, Northwest Syria -- Experimental Analysis of Sun-Dried Bricks and Pottery from the Ubaid and Late Chalcolithic Periods -- Prehistoric Mining and Metallurgy in Uzbekistan: An Introduction -- Fortifications and the Defensive Landscapes of Kalat (North-Eastern Iran) -- South-Central Anatolia during the Iron Ages: a diachronic view from Kınık Höyük (Niğde).